Pseudo-cobra neck deformity due to aplasia cutis congenita. (December 2020) - Feit, Noah Z.; Davison, Wesley L.; Sclafani, Anthony P.; Modi, Vikash K.
Abstract: Aplasia cutis congenita is a rare but heterogeneous group of conditions characterized by the absence of one or more areas of skin sometimes extending to deeper tissues. The disorder as a solitary neck lesion has yet to be reported in the literature. Our patient presented with a pseudo-cobra neck deformity secondary to aplasia cutis congenita. Guidance on optimal management for non-scalp and more "benign" presentations of this disorder is lacking.